2020
DOI: 10.1016/j.immuni.2020.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Polyamine Generation in Keratinocytes Promotes Self-RNA Sensing by Dendritic Cells in Psoriasis

Abstract: The mechanisms underlying tissue-specific chronic inflammation are elusive. Here we report that mice lacking Protein Phosphatase in keratinocytes are predisposed to psoriasis-like skin inflammation, with an inordinate urea cycle and enhanced oxidative phosphorylation that supports hyperproliferation. This phenotype is mediated by increased Arginase-1 production resulting from CCAAT/enhancer-binding protein beta activation. Single-cell RNA-seq of the psoriatic epidermis revealed that the rate-limiting enzyme fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 63 publications
3
59
0
Order By: Relevance
“…IL-17A plays an essential role in inflammation, metabolism, and bone/joint damage (8,10,15,(60)(61)(62). The IL-17 levels and Th17 cell frequencies are high in the skin, synovial fluid, and synovium tissue of the patients with psoriatic arthritis (PsA) (18,(63)(64)(65).…”
Section: Role Of Il-17 Family Members In Psoriasismentioning
confidence: 99%
“…IL-17A plays an essential role in inflammation, metabolism, and bone/joint damage (8,10,15,(60)(61)(62). The IL-17 levels and Th17 cell frequencies are high in the skin, synovial fluid, and synovium tissue of the patients with psoriatic arthritis (PsA) (18,(63)(64)(65).…”
Section: Role Of Il-17 Family Members In Psoriasismentioning
confidence: 99%
“…LL37 was reported to form complexes with selfderived RNA as well as self-derived DNA, triggering TLR7 and TLR8 activation in human DCs, which may be associated with psoriasis pathogenesis (221). Another study showed that together with cargo peptides, polyamines form a complex with RNA, promoting endosomal uptake and activation of TLR7 in DCs (222). The decreased expression of protein phosphatase 6 was observed in psoriatic lesions, leading to an increased generation of arginase-1-mediated polyamine.…”
Section: Inflammation Induced By Self-derived Nucleic Acid Recognition In Other Common Diseasesmentioning
confidence: 99%
“…Conversely, hyperactive arginine metabolism and excessive polyamine production have been observed in psoriasis, an incurable chronic inflammatory disease [132]. Specifically, deficiency in protein phosphatase 6 (PP6) disables skin homeostasis and this has been shown to involve increased ARG1 transcription via phosphorylation and activation of the C/EBP-β transcription factor, and increased production of polyamines.…”
Section: Control Of Polyamine Homeostasis and Interacting Metabolic Pathways In Cancermentioning
confidence: 99%